Polycystin-1 and polycystin-2 are involved in the acquisition of aggressive phenotypes in colorectal cancer. - Gargalionis, Antonios N; Korkolopoulou, Penelope; Farmaki, Elena; Piperi, Christina; Dalagiorgou, Georgia; Adamopoulos, Christos; Levidou, Georgia; Saetta, Angelica; Fragkou, Paraskevi; Tsioli, Panagiota; Kiaris, Hippokratis; Zizi-Serbetzoglou, Adamantia; et al. (Int J Cancer, 2015)
The polycystins PC1 and PC2 are emerging as major players in mechanotransduction, a process that influences all steps of the invasion/metastasis cascade. We hypothesized that PC1 and PC2 facilitate cancer aggressiveness. Immunoblotting, RT-PCR, semi-quantitative and quantitative real-time PCR and FACS analyses were employed to investigate the effect of polycystin overexpression in colorectal cancer (CRC) cells. The impact of PC1 inhibition on cancer-cell proliferation was evaluated through an MTT assay. In vitro data were analyzed by Student's t-test. HT29 human xenografts were treated with anti-PC1 (extracellular domain) inhibitory antibody and analyzed via immunohistochemistry to determine the in vivo role of PC1 in CRC. Clinical significance was assessed by examining PC1 and PC2 protein expression in CRC patients (immunohistochemistry). In vivo and clinical data were analyzed by non-parametric tests, Kaplan-Meier curves, log-rank test and Cox model. All statistical tests were two-sided. PC1 overexpression promotes epithelial-to-mesenchymal transition (EMT) in HCT116 cells, while PC2 overexpression results in upregulation of the mTOR pathway in SW480 cells. PC1 inhibition causes reduced cell proliferation in CRC cells inducing tumor necrosis and suppressing EMT in HT29 tumor xenografts. In clinical study, PC1 and PC2 overexpression associates with adverse pathological parameters, including invasiveness and mucinous carcinomas. Moreover, PC1 overexpression appears as an independent prognostic factor of reduced recurrence-free survival (HR = 1.016, p = 0.03) and lowers overall survival probability, while aberrant PC2 expression predicts poor overall survival (p = 0.0468). These results support, for the first time, a direct link between mechanosensing polycystins (PC1 and PC2) and CRC progression.
Keywords: Aged; Aged, 80 and over; Animals; Cell Line, Tumor; Cell Proliferation; Colorectal Neoplasms; Disease Models, Animal; Disease Progression; Epithelial-Mesenchymal Transition; Female; gene expression; Heterografts; Humans; Immunohistochemistry; Lymphatic Metastasis; Male; Mice; Microsatellite Instability; Middle Aged; Neoplasm Grading; Neoplasm Staging; Phenotype; Prognosis; signal transduction; TOR Serine-Threonine Kinases; TRPP Cation Channels; Tumor Burden